Association between leptin, body composition, sex and knee cartilage morphology in older adults: the Tasmanian older adult cohort (TASOAC) study. Issue 9 (3rd January 2008) - Ding, C; Parameswaran, V; Cicuttini, F; Burgess, J; Zhai, G; Quinn, S; Jones, G
Abstract : Objective: To describe the associations between leptin, body composition, sex and knee cartilage volume/defects in older adults. Methods: A cross-sectional sample of 190 randomly selected subjects (mean 63 years, range 52–78, 48% female) were studied. Knee cartilage volume and defects were determined using T1-weighted fat saturation MRI. Serum leptin levels were measured by radioimmunoassay. Fat and lean mass were measured by dual energy x ray absorptiometry (DXA). Body mass index (BMI) was calculated. Results: In multivariable analysis, serum levels of leptin were negatively associated with total cartilage volume (β: −541 mm3 /log transformed unit, 95% CI −861 to −221) but not with prevalent knee cartilage defects. BMI was negatively associated with cartilage volume after adjustment for total lean mass and positively with prevalent knee cartilage defects. However, the association between BMI and cartilage volume disappeared after adjustment for leptin while the association between BMI and cartilage defects remained unchanged. Lastly, sex differences in total cartilage volume decreased substantially after adjustment for leptin (R2 from 51% to 30%). Conclusions: This cross-sectional study suggests cartilage volume loss with obesity and female sex is related to leptin and, thus, is hormonally mediated in older adults. By contrast, obesity related knee focal cartilage defects may be more related to non-hormonal factors.